ANALISIS KINERJA RANTAI PASOK TANDAN BUAH SEGAR (TBS) PADA PT TASMA PUJA SEI KUAMANG KABUPATEN KAMPAR - Andri Walchred; Suarni Norawati (Jurnal Riset Manajemen Indonesia, 2020)
The performance of Fresh Fruit Bunch reception activities from the plantation is not good, where out of the 6 years supply of FFB receipts, only 5 years were able to reach the set budget targets in 2013, 2014, 2015, 2017, while the worst performance occurred in 2016 and 2018 where the performance of FFB reception activities is below 80%. The performance of sorting and boiling stages at PT. Tasma Puja in 2013 to 2018 can be considered quite good where the number of ready-made fruit if it reaches more than 90%, meaning that the loss of fruit weight only occurs no more than 10%. This is consistent with the budget target set at the time of receipt of FFB from suppliers, where the weight of the scales received by the company will be reduced by the estimated loss of fruit weight by 10%.